Misalignment among adolescents living with obesity, caregivers, and healthcare professionals: ACTION Teens global survey study - BEREKET, ABDULLAH (My University, 2022)
Background There is limited evidence regarding the experiences, challenges, and needs of adolescents living with obesity (ALwO), their caregivers, and healthcare professionals (HCPs). Objectives The cross-sectional, survey-based global ACTION Teens study aimed to identify perceptions, attitudes, behaviours, and barriers to effective obesity care among ALwO, caregivers of ALwO, and HCPs. Methods ALwO (aged 12 to N = 5275), caregivers (N = 5389), and HCPs treating ALwO (N = 2323) from 10 countries completed an online survey (August-December 2021). Results Most ALwO perceived their weight as above normal (76% vs. 66% of caregivers), were worried about its impact on their health (85% vs. 80% of caregivers), and recently made a weight loss attempt (58%). While 45% of caregivers believed ALwO would slim down with age, only 24% of HCPs agreed. Most commonly reported weight loss motivators for ALwO were wanting to be more fit/in better shape according to ALwO (40%) and caregivers (32%), and improved confidence/social life according to HCPs (69%). ALwO weight loss barriers included lack of hunger control (most commonly reported by ALwO/caregivers), lack of motivation, unhealthy eating habits (most commonly agreed by HCPs), and lack of exercise. Conclusions Misalignment between ALwO, caregivers, and HCPs-including caregivers\" underestimation of the impact of obesity on ALwO and HCPs\" misperception of key motivators/barriers for weight loss-suggests a need for improved communication and education.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Medicine; Health Sciences; Internal Medicine Sciences; Child Health and Diseases; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics; Pediatrics, Perinatology and Child Health; adolescents; clinical care; family practice; obesity treatment; physician attitudes; CHILDHOOD OBESITY; CHILDREN